2011
DOI: 10.1186/1477-7819-9-113
|View full text |Cite
|
Sign up to set email alerts
|

A review of duodenal metastases from squamous cell carcinoma of the cervix presenting as an upper gastrointestinal bleed

Abstract: Upper gastrointestinal bleeding due to duodenal metastases is extremely uncommon. Extra-pelvic spread of squamous cell carcinoma (SCC) of the cervix to the small bowel is rare with only 6 reported cases in the English literature since 1981(PubMed, Medline).We report the case of a 49-year-old woman who presented with upper-gastrointestinal bleeding two years after the diagnosis of SCC of the cervix. At esophagogastroduodenoscopy, there was a stricture in the second part of the duodenum which was biopsied for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 13 publications
1
45
1
8
Order By: Relevance
“…In previous reports, metastasis of cervical cancer to the duodenum and spleen has been reported. [2][3][4] We herein report the first case of isolated jejunal metastases from early-stage cervical cancer, which was confirmed …”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In previous reports, metastasis of cervical cancer to the duodenum and spleen has been reported. [2][3][4] We herein report the first case of isolated jejunal metastases from early-stage cervical cancer, which was confirmed …”
Section: Introductionsupporting
confidence: 56%
“…Such spread is believed to occur commonly through the lymphatics, usually the para-aortic or mesenteric nodes to the bowel's serosa and less often via the blood stream or by peritoneal seeding. 3,4 Only seven cases have been reported for SCC of the cervix with documented metastases to the small bowel, 3 and there is only one published case report of a cervical cancer metastasizing to the jejunum. 9 Misonou et al 9 reported a case with stage IA cervical cancer recurring 13 years after hysterectomy with multiple metastases to the jejunum, which caused small intestinal perforation.…”
Section: Fig 3 -(A) Histopathological Appearance Of the Jejunum [Hemmentioning
confidence: 98%
“…Although cervical cancer death rates have been decreasing, the recurrence and metastasis of cervical carcinoma to other sites such as the lymph nodes [2,3], lungs [4,5], bones [6,7], liver [8], and bowels [9] are critical factors contributing to mortality in cervical cancer patients. Therefore, apart from surgery and the destruction of cervical cancer cells by medication, inhibiting metastasis is an auxiliary strategy for curing patients of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Kanthan et al . adopted CK5, p63 and p16 as immunohistochemical markers to confirm the diagnosis of SCC of the cervix metastatic to the duodenum [15]. Strikingly, Gevaert et al .…”
Section: Discussionmentioning
confidence: 99%